STAGES OF THE DEVELOPMENT OF PRIMARY EDUCATION CONTENT AND MODERN REQUIREMENTS - Ruzmetova Novval Vahabdjanovna; Axmedova Shaydogul Oybek qizi (Bright Mind Publishing, 2026)
The content of primary education has undergone significant changes in accordance with societal development, educational reforms, and modern pedagogical demands. This article analyzes the main stages of the development of primary education content and identifies current requirements for its improvement. Special attention is given to the transition from traditional knowledge-based curricula to competency-based and learner-centered approaches. Modern requirements such as the development of critical thinking, creativity, digital literacy, and interdisciplinary integration are highlighted. The study emphasizes the importance of aligning primary education content with international standards while preserving national educational values. The findings contribute to improving the quality and effectiveness of primary education in contemporary educational systems.
Keywords: Primary education, curriculum development, stages of educational content, modern educational requirements, competency-based education, learner-centered approach, critical thinking, creativity, digital literacy.